2008
DOI: 10.1186/1471-230x-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Rebleeding rate after interventional therapy directed by capsule endoscopy in patients with obscure gastrointestinal bleeding

Abstract: Background: The precise role of capsule endoscopy in the diagnostic algorithm of obscure gastrointestinal bleeding has yet to be determined. Despite the higher diagnostic yield of capsule endoscopy, the actual impact on clinical outcome remains poorly defined. The aim of this study was to evaluate the follow-up results of patients with obscure gastrointestinal bleeding to determine which management strategies after capsule endoscopy reduced rebleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 32 publications
9
36
2
2
Order By: Relevance
“…Albert et al (22) found that VCE results determined the therapy in 66% of the cases and led to an alteration in management in 32.3% of the cases. In accordance, Endo et al (33) found that the re-bleeding rate of patients who underwent therapeutic intervention after positive VCE small bowel exam was significantly lower (9.5% vs. 40.0%, P=0.046) than that of those who did not undergo treatment. Consistently, Park et al (34) demonstrated that when specific treatment after VCE (DBE not included) was applied, a significant decrease in re-bleeding was noted (HR: 0.111; 95% CI, 0.013-0.980; P=0.043).…”
Section: Impact On Subsequent Therapeutic Strategies and Clinical Outsupporting
confidence: 62%
See 1 more Smart Citation
“…Albert et al (22) found that VCE results determined the therapy in 66% of the cases and led to an alteration in management in 32.3% of the cases. In accordance, Endo et al (33) found that the re-bleeding rate of patients who underwent therapeutic intervention after positive VCE small bowel exam was significantly lower (9.5% vs. 40.0%, P=0.046) than that of those who did not undergo treatment. Consistently, Park et al (34) demonstrated that when specific treatment after VCE (DBE not included) was applied, a significant decrease in re-bleeding was noted (HR: 0.111; 95% CI, 0.013-0.980; P=0.043).…”
Section: Impact On Subsequent Therapeutic Strategies and Clinical Outsupporting
confidence: 62%
“…Endo and associates (33) found significantly higher rate of re-bleeding in patients with negative VCE, compared to those with significant findings (50% vs. 12%). Authors concluded that VCE negative patients should undergo regular follow-up, whilst being mindful that the bleeding may not originate from the small bowel.…”
Section: Re-bleeding Rate After Index Vce Small Bowel Examinationmentioning
confidence: 80%
“…With regards to rebleeding rates, Endo et al [18] found that among patients with significant CE findings, the rebleeding rate at a mean of 11.6 mo follow up of the patients who underwent therapeutic intervention was significantly lower than that of those without intervention (9.5% vs 40.0%, P = 0.046). This is supported by other studies [83,84] .…”
Section: Capsule Endoscopymentioning
confidence: 99%
“…CE enables direct visualisation of the small bowel mucosa and has a high sensitivity for detecting flat lesions, such as angiodysplasias, ulcers and arteriovenous malformations which are not easily detectable on radiological modalities [15] . The reported diagnostic yield in literature ranges from 58.4% to 86.8% [9,14,[16][17][18][19][20][21] . The wide range is attributable to different definitions of a positive finding on CE.…”
Section: Capsule Endoscopymentioning
confidence: 99%
See 1 more Smart Citation